The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1121/1.3050304
|View full text |Cite
|
Sign up to set email alerts
|

Detecting incipient inner-ear damage from impulse noise with otoacoustic emissions

Abstract: Audiometric thresholds and otoacoustic emissions (OAEs) were measured in 285 U.S. Marine Corps recruits before and three weeks after exposure to impulse-noise sources from weapons' fire and simulated artillery, and in 32 non-noise-exposed controls. At pre-test, audiometric thresholds for all ears were Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 60 publications
4
67
1
2
Order By: Relevance
“…While a 10e11% rate of STS from noise exposure during recruit training is the norm (Marshall et al, 2009), our study population exhibited a greater than 37% rate of STS despite strict use of HPDs and a highly controlled environment free of other significant noise outside the weapons training period. The most likely reason for this high rate of threshold shift is that, in addition to the standard audiometric frequencies tested in other studies (Marshall et al, 2009), this study also measured hearing thresholds at high frequencies between 2 kHz and 20 kHz, inclusive.…”
Section: Discussionmentioning
confidence: 98%
“…While a 10e11% rate of STS from noise exposure during recruit training is the norm (Marshall et al, 2009), our study population exhibited a greater than 37% rate of STS despite strict use of HPDs and a highly controlled environment free of other significant noise outside the weapons training period. The most likely reason for this high rate of threshold shift is that, in addition to the standard audiometric frequencies tested in other studies (Marshall et al, 2009), this study also measured hearing thresholds at high frequencies between 2 kHz and 20 kHz, inclusive.…”
Section: Discussionmentioning
confidence: 98%
“…However, ears in this category are already known to be more at risk for incipient NIHL from both continuous-noise and impulse-noise sources (Lapsley Miller et al, 2006;Job et al, 2009;Marshall et al, 2009). Our working presumption is that these low-level OAEs are due to subclinical damage to the inner ear that has not yet shown a significant change on an audiogram.…”
Section: A Clinical Assay For Hcpsmentioning
confidence: 99%
“…It is thus interesting to speculate that a simple test of aural-distortion judgments might provide some indication of the ear's susceptibility to hearing damage from noise exposure. In a recent report, Marshall et al (2009) found evidence that high-frequency otoacoustic emission levels may be correlated to differences in susceptibility to hearing damage. It is tempting to assume that the same intermodulation-distortion mechanism in the mechanics of the cochlea produces audible harshness at high sound levels and measurable otoacoustic emissions at lower sound levels.…”
Section: Absence Of "Fortissimo Blare" From Aural Distortionmentioning
confidence: 99%